(3GdUGaj aj JaSQ GdbQBf GdcQjes - (3GdcGTGfj, edG eMSf GdcGTGfj, eMeO Hf eQJVi, cGf MkjG (B1065(3g` (B1655(3es
(3ChdgG (B:s
(3ChdgG(B: (3ShQI Gdcga, HSe Gddg GdQMef GdQMje, GdMeO ddg GdPj CfRd Ydi YHOg GdcJGH, jYfj GdbQBf, Yde Gddg SHMGfg YHGOg cja jMeOhfg Ydi CLd fYeI Ydjge GdPj gh SHH fLGJges
(3BNQgG (B:s
(3BNQgG(B: (3GdPj gh YHGQI Yf YOe GddjGbI dgG hjMed GdEfSGf EjGgG HMedg dgG ef ZjQ GSJMbGb JcHQG Ydi CgdgG Ch eY JbUjQg HMSH hSYg aj COGFgGs
(3JHUQI GdeDda (B:s
(3CQN UGMH GdPQjYI haGJg SfI (B1091(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 710s
(3GdPQjYI, L (B15: 6s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs